Development of the students' mathematical self-efficacy in learning space analytic geometry - La Moma; Widya Putri Ramadhani (International Journal of Trends in Mathematics Education Research, 2022)
Self-Efficacy is one of the factors that support the success of students in participating in the lecture process, but this is not paid much attention to, causing students to experience low grades and have not been able to develop themselves. This study was conducted to see the achievement self-efficacy of students who offer space analytic geometry courses and the achievement of the dimensions self-efficacy of students who offer space analytic geometry courses. The purpose of this study was to determine the achievement self-efficacy dimensions self-efficacy in learning space analytic geometry. The type of research used is descriptive quantitative and qualitative research. The subjects of this study consisted of 62 students for the 2020/2021 academic year who were selected from high, medium, and low ability levels. From the results of data analysis, it was found that: (1) the achievement of self-efficacy in learning space analytic geometry was included in the medium category, and (2) the achievement of each dimension of self-efficacy in learning space analytic geometry was also included in the medium category.